Efficacy and safety of local lysozyme treatment in patients with oral mucositis after chemotherapy and radiotherapy - Eminagić Dzenana; Lokvančić Aida; Hasanbegović Berisa; Mekić-Abazović Alma; Avdičević Asmir; Marijanović Inga; Janković Slobodan M.; Kapo Belma (Acta Pharmaceutica)
This observational clinical study was composed of two substudies: a non-comparative one (n = 166), testing only lysozyme-based compounds (LBCs), and a comparative substudy (n = 275), testing both LBCs and bicarbonate-based local compounds (BBCs) on the healing of oral mucositis during radio- or chemotherapy. The density of ulcerations has decreased significantly after the treatment with lysozyme in both substudies. The density of ulcerations in the radiotherapy group was lower in patients treated with LBCs compared to patients treated with BBCs (p < 0.001). In the chemotherapy group, reduction of ulceration density was similar with both LBCs and BBCs. The LBCs reduced pain intensity during the intake of solid food and speech more than BBCs in both patient cohorts (p < 0.05). In the radiotherapy cohort, pain intensity when consuming liquid foods was reduced more with LBCs than with BBCs (p < 0.05). No adverse events were recorded. This study demonstrates the advantages of treating oral mucositis during radiotherapy or chemo-therapy with LBCs.